A new predator connecting the abyssal with the hadal in the Kuril-Kamchatka Trench, NW Pacific - Anne-Nina Lörz; Anna Maria Jażdżewska; Angelika Brandt (PeerJ, 2018)
The bathyal to hadal deep sea of north-west Pacific Ocean was recently intensively sampled during four international expeditions (KuramBio I and II, SoJaBio and SokhoBio). A large amphipod, Rhachotropis saskia n. sp., was sampled in the Kuril-Kamchatka Trench and increases the number of described hadal species of that area to eight. A detailed description of the new species is provided, including illustrations, scanning-microscope images and molecular analysis. This predatory species was sampled at both continental and ocean abyssal margins of the Kuril-Kamchatka Trench as well as at hadal depths of the trench. The wide bathymetric distribution of the new species over more than 3,000 m is confirmed by molecular analysis, indicating that the Kuril Kamchatka Trench is not a distribution barrier for this species. However, the molecular analysis indicated the presence of isolation by distance of the populations of the studied taxon.